2021
DOI: 10.1080/14756366.2021.1900159
|View full text |Cite
|
Sign up to set email alerts
|

Platelet hyaluronidase 2 enrichment in acute coronary syndromes: a conceivable role in monocyte-platelet aggregate formation

Abstract: Acute Coronary Syndromes (ACS) with plaque erosion display dysregulated hyaluronan metabolism, with increased hyaluronidase-2 (HYAL2) expression. However, the expression and the role of this enzyme on platelets has never been explored. We evaluated the platelet’s HYAL2 ( plt HYAL2) levels on I) stable angina (SA) and II) ACS patients, furtherly sub-grouped in Intact-Fibrous-Cap (IFC) and Ruptured-Fibrous-Cap (RFC), according to Optical Coherence Tomography. We assessed the HYAL2 role thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 18 publications
1
5
0
Order By: Relevance
“…Differences in innate and adaptive immune system have been described in ACS patients (Liuzzo et al, 2007(Liuzzo et al, , 2020Flego et al, 2016;Leers et al, 2017;Pedicino et al, 2018a;Leistner et al, 2020). Starting from PBMCs as source material, our group documented an altered hyaluronan metabolism in NSTE-ACS patients presenting with plaque erosion (Pedicino et al, 2018b), further confirmed by later investigations on platelets and monocyte-platelet interaction (Vinci et al, 2021). Those findings pointed the attention to the extracellular matrix derangement and its altered components (Angelini et al, 2018).…”
Section: Discussionsupporting
confidence: 64%
“…Differences in innate and adaptive immune system have been described in ACS patients (Liuzzo et al, 2007(Liuzzo et al, , 2020Flego et al, 2016;Leers et al, 2017;Pedicino et al, 2018a;Leistner et al, 2020). Starting from PBMCs as source material, our group documented an altered hyaluronan metabolism in NSTE-ACS patients presenting with plaque erosion (Pedicino et al, 2018b), further confirmed by later investigations on platelets and monocyte-platelet interaction (Vinci et al, 2021). Those findings pointed the attention to the extracellular matrix derangement and its altered components (Angelini et al, 2018).…”
Section: Discussionsupporting
confidence: 64%
“…HYAL2 (hyaluronidase 2) is related to inflammatory responses and cardiometabolic pathology. Expression of HYAL2 has been linked to acute coronary syndromes (Vinci et al, 2021) and inflammatory cytokines, chemokines, and angiogenic factors in bladder cancer tissue (Dominguez‐Gutierrez et al, 2021). KCNJ16 ( potassium inwardly rectifying channel subfamily J member 16) is important for potassium transport into kidney cells and has been associated with metabolic acidosis (Webb et al, 2021) as well as hypotension, hypokalemia, and associated mortality in rats fed a high salt diet (Palygin et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…HYAL2 (hyaluronidase 2) is related to inflammatory responses and cardiometabolic pathology. Expression of HYAL2 has been linked to acute coronary syndromes (Vinci et al, 2021) and inflammatory cytokines, chemokines, and angiogenic factors in bladder cancer tissue (Dominguez-Gutierrez et al, 2021). KCNJ16…”
Section: Inflammation Immune Function and Accelerated Agingmentioning
confidence: 99%
“…Notably, only one gene of our array, HYAL2, originally involved in hyaluronan catabolism and glycocalyx impairment [ 27 , 28 , 29 ], displayed an increased expression in PBMCs of INOCA patients. HYAL2 has been studied in the context of shear stress and plaque erosion [ 27 , 30 , 31 ]; however, no study before has investigated HYAL2 in INOCA patients. The endothelium bears a crucial aspect in vascular tone modulation.…”
Section: Discussionmentioning
confidence: 99%